Overexpression of Enterococcus faecalis elr operon protects from phagocytosis - Cortes-Perez, Naima G. (BMC Microbiol, 2015)
BACKGROUND: Mechanisms underlying the transition from commensalism to virulence in Enterococcus faecalis are not fully understood. We previously identified the enterococcal leucine-rich protein A (ElrA) as a virulence factor of E. faecalis. The elrA gene is part of an operon that comprises four other ORFs encoding putative surface proteins of unknown function. RESULTS: In this work, we compared the susceptibility to phagocytosis of three E. faecalis strains, including a wild-type (WT), a ΔelrA strain, and a strain overexpressing the whole elr operon in order to understand the role of this operon in E. faecalis virulence. While both WT and ΔelrA strains were efficiently phagocytized by RAW 264.7 mouse macrophages, the elr operon-overexpressing strain showed a decreased capability to be internalized by the phagocytic cells. Consistently, the strain overexpressing elr operon was less adherent to macrophages than the WT strain, suggesting that overexpression of the elr operon could confer E. faecalis with additional anti-adhesion properties. In addition, increased virulence of the elr operon-overexpressing strain was shown in a mouse peritonitis model. CONCLUSIONS: Altogether, our results indicate that overexpression of the elr operon facilitates the E. faecalis escape from host immune defenses. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12866-015-0448-y) contains supplementary material, which is available to authorized users.